Moments of clarity : voices from the front lines of addiction and recovery - Lawford, Christopher Kennedy, 1955- (New York, NY : William Morrow, 2009)
The author of the "New York Times" bestseller "Symptoms of Withdrawal" explores the shift in time and perception from addiction to recovery based on his own experiences and those of other recovered addicts from all walks of life.
Jim Vance -- Susan Cheever -- Chris Gerolmo -- Aimee Liu -- Ron Smith -- David Black -- Alec Baldwin -- Judy Collins -- Mike Binder -- Dallas Taylor -- Ed Begley, Jr. -- Kelly McGillis -- Gerry Cooney -- Steve Earle -- Stephen Bergman and Janet Surrey -- Richard Dreyfuss -- David James Elliott -- Tom Arnold -- Velvet Mangan -- Jamie Lee Curtis -- Earl Hightower -- Chris Mecham -- Karl Fleming -- Larry Kudlow -- Lou Gossett, Jr. -- Malachy McCourt -- Greg Behrendt -- Marie Morning-Glory -- Thomas Henderson -- Mike Early -- Denny Seiwell -- Michael Glasser -- Bob Timmons -- Rudy Tomjanovich -- Richard Lewis -- Katey Sagal -- Jim Ramstad -- Kale Browne -- Martin Sheen -- Max Cleland -- Elaine Stritch -- DeJuan Verrett.
Keywords: Lawford, Christopher Kennedy, -- 1955-; Recovering addicts -- United States -- Biography; Actors -- United States -- Biography